Kraft scrap paper pulp as a substitute of wood chips in manufacture of particleboards resinated with hybrid pf/pmdi resin - Dukarska, Dorota; Buszka, Katarzyna; Modzelewska, Izabela (Maderas. Ciencia y Tecnología, 2018)
This study analyzed feasibility of manufacture of composite particleboards resinated with a mixture of phenol–formaldehyde resin and 4,4′-methylenediphenyl isocyanate in the weight ratio 70:30. For this purpose 3-layer particleboards were produced with varying shares of Kraft scrap paper pulp in the core. Experimental boards were manufactured applying 0, 10, 15, 25, 50 and 75% substitution of wood chips with Kraft paper pulp. Analyses were conducted to determine physico-mechanical properties of boards, i.e. bending strength, modulus of elasticity, internal bond before and after the boiling test and swelling in thickness after 24 soaking in water. Based on recorded testing results it was stated that moisture resistant composite boards manufactured with a 25% substitution of wood chips with Kraft paper pulp meet the requirements of the EN 312 standard for boards used in humid conditions in terms of their strength and moisture resistance specified in the internal bond after the boiling test.